Developing a Model for Audit Documentation Quality Using Internet-Based Technologies Based on a Grounded Theory Approach - Peyvandi, Paniz; Yalfani, Amir; Fazeli, Naghi (Management Strategies and Engineering Sciences, 2024)
The present study aims to develop a model for audit documentation quality using internet-based technologies based on a grounded theory approach. Methodologically, the study is descriptive-analytical and, in terms of its purpose, practical. Data collection methods include library research and field studies. In the qualitative phase, data collection tools included observations and interviews, while in the quantitative phase, a questionnaire was employed. The qualitative statistical population consisted of experts and specialists affiliated with the Iranian Association of Auditing. Data analysis from each in-depth interview was conducted using purposive snowball sampling until theoretical saturation and data adequacy were achieved (20 interviews were conducted to reach theoretical saturation). Sampling in the qualitative phase was performed non-probabilistically and purposively. In the quantitative phase of the study, aimed at validating the final model, the statistical population included all auditors from selected and accredited firms. The sample size for this phase was calculated using Cochran's formula, resulting in 373 participants. A combination of qualitative and quantitative methods was employed for analysis. In the qualitative phase, in-depth interview techniques were used, and in the quantitative phase, interpretive structural modeling (ISM), structural equations modeling (SEM), and fuzzy DEMATEL and fuzzy ANP techniques were applied. Using the interview technique, nine criteria were identified, and strategies for audit documentation quality using internet-based technologies were proposed based on a grounded theory approach. Interpretive structural modeling and structural equations modeling elucidated the relationships between variables and the preliminary model framework. The fuzzy DEMATEL results revealed that "organizational factors" had the most significant impact on audit documentation quality using internet-based technologies compared to other factors, with "managerial factors" ranking second. Additionally, "supervisory and technological factors" were the most influenced by other factors. Fuzzy ANP results indicated that organizational factors were the highest priority, followed by long-term relationships, with other criteria ranking third.